Effectiveness of Gestalt Theory-Based Counseling in Reducing Delinquency Among Junior High School Students - Hardimen Tanjung; Basrizal Yasraf Koto (Acta Psychologia, 2023)
This study investigates the relationship between the implementation of Gestalt theory-based counseling and the reduction in delinquency among junior high school (SMP) students. A quasi-experimental design was employed, dividing participants into intervention and control groups. The intervention group received regular counseling sessions based on Gestalt principles, while the control group received standard counseling or no additional interventions. Pre- and post-intervention assessments were conducted using surveys, behavioral observations, interviews, and standardized instruments to measure delinquency and counseling effectiveness. Quantitative analysis revealed a statistically significant reduction in delinquency levels among students receiving Gestalt-based counseling compared to the control group (p < 0.05). Students in the intervention group exhibited a substantial decrease in delinquent behaviors, with qualitative data supporting improved emotional regulation, conflict resolution skills, and heightened self-awareness.